2019
DOI: 10.1016/j.jhepr.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Continuous terlipressin infusion is associated with improved diet intake and muscle strength in patients awaiting liver transplant

Abstract: Highlights • Malnutrition and poor muscle strength are highly prevalent in cirrhotics with hepatorenal syndrome. • Terlipressin infusion increased energy and protein intake in patients with hepatorenal syndrome. • Handgrip strength continued to increase with every day of terlipressin therapy • Medium to long-term terlipressin infusion was safe and efficacious as a bridge to liver transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…As the volume under minimal surface depends upon the turning point of the minimal surface, hence we shall first compute the change in turning point. To begin with let us first compute the length l of the subsystem perturbatively in the same limit as in eq.no (28) up to second order. The expression for length of the subsystem when the strip is perpendicular to the direction of boost is given by…”
Section: Holographic Subregion Complexity Upto Second Order In Perturmentioning
confidence: 99%
“…As the volume under minimal surface depends upon the turning point of the minimal surface, hence we shall first compute the change in turning point. To begin with let us first compute the length l of the subsystem perturbatively in the same limit as in eq.no (28) up to second order. The expression for length of the subsystem when the strip is perpendicular to the direction of boost is given by…”
Section: Holographic Subregion Complexity Upto Second Order In Perturmentioning
confidence: 99%
“…The last term in (2.1) is the null fluid action. In order to construct an uncharged null fluid collapse, following the discussion in [45], we can build the action by…”
Section: Charged Ads-vaidya Spacetimementioning
confidence: 99%
“…In Refs. [45,46], Chapman et al investigated the CA and CV conjectures for AdS-Vaidya spacetime which is sourced by the collapse of a spherically symmetric thin shell of null fluid [47][48][49]. They found that the standard definition of the WDW action is not appropriate for these dynamical spacetimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above expression c 1 is arbitrary integration constant. Substituting (27) and (28) in (16), up to first order inμ, we have…”
Section: Optimizing Various States In T T Deformed Cftsmentioning
confidence: 99%